(untitled) (Journal of Veterinary Medicine and Animal Production, 2022)
In a preliminary study, forty adult apparently healthy Nubian nanny goats (20 kept indoor and 20 roaming outdoor) sera samples collected from Atbara area, River Nile State were analyzed to compare the serum concentration of the fallowing trace elements: Co, Cr, Cu, Fe and Mn using Atomic Absorption Spectrophotometer (AAS). The results showed a significantly (P < 0.05) higher values of serum Cr and Fe concentrations in goats kept indoor and a significantly (P < 0.05) higher serum Cu and Mn concentrations in goats roaming outdoor. There was no significant difference (P > 0.05) in serum Co concentration between the two groups.